Evaluation of Long-Time Decoction-Detoxicated Hei-Shun-Pian (Processed Aconitum carmichaeli Debeaux Lateral Root With Peel) for Its Acute Toxicity and Therapeutic Effect on Mono-Iodoacetate Induced Osteoarthritis - Lei Zhang; Ting Li; Rongrong Wang; Jiaan Xu; Li Zhou; Li Yan; Zhengyan Hu; Hongwen Li; Fucun Liu; Wenxi Du; Peijian Tong; Huiling Wu; et al. (Frontiers Media S.A., 2020)
BackgroundAs a degenerative joint disease with severe cartilage destruction and pain, osteoarthritis (OA) has no satisfactory therapy to date. In traditional Chinese medicine (TCM), Aconitum carmichaeli Debeaux derived Hei-shun-pian (Hsp) has been developed for joint pain treatment. However, it causes adverse events in OA patients. Long-time decoction has been traditionally applied to reduce the aconite toxicity of Hsp and other aconite herbs, but its detoxifying effect is uncertain.MethodsHsp was extracted with dilute decoction times (30, 60, and 120 min) and evaluated by toxicological, chemical, pharmacological assays. Acute toxicity assay and chemical analysis were employed to determine the toxicity and chemoprofile of Hsp extracts, respectively. Since the detoxified Hsp (dHsp) was defined, its therapeutic effect was evaluated by using an OA rat model induced by monosodium iodoacetate. dHsp at 14 g/kg was orally administered for 28 days, and the pain assessments (mechanical withdrawal threshold and thermal withdrawal latency) and histopathological analyses (HE and safranin-O staining) were performed. Real-time PCR (qPCR) was applied to determine the molecular actions of dHsp on cartilage tissue and on chondrocytes. MTT assay was conducted to evaluate the effect of dHsp on the cell viability of chondrocytes. The cellular and molecular assays were also conducted to analyze the functions of chemical components in dHsp.ResultsThe chemoprofile result showed that the contents of toxic alkaloids (aconitine, mesaconitine, and hypaconitine) were decreased but that of non-toxic alkaloids (benzoylaconitine, benzoylmesaconitine, and benzoylhypaconitine) were increased with increasing decoction time. Acute toxicity assay showed that only Hsp extract with 120 min decoction was non-toxic within the therapeutic dose range. Thus, it was defined as dHsp for further experiment. In OA experiment, dHsp significantly attenuated joint pain and prevented articular degeneration from MIA attack. qPCR data showed that dHsp restored the abnormal expressions of Col10, Mmp2, Sox5, Adamts4/5/9, and up-regulated Col2 expression in rat cartilage. In vitro, dHsp-containing serum significantly proliferated rat chondrocytes and regulated the gene expressions of Col2, Mmp1, Adamts9, and Aggrecan in a similar way as the in vivo data. Moreover, aconitine, mesaconitine, and hypaconitine exerted cytotoxic effects on chondrocytes, while benzoylaconitine and benzoylhypaconitine except benzoylmesaconitine exhibited similar molecular actions to dHsp, indicating contributions of benzoylaconitine and benzoylhypaconitine to dHsp.ConclusionsThis study defined dHsp and demonstrated dHsp as a potential analgesic and disease modifying agent against OA with molecular actions on the suppression of chondrocyte hypertrophy and extracellular matrix degradation, providing a promising TCM candidate for OA therapy.